2012
DOI: 10.1503/cjs.000711
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lateral thermal damage of the human peritoneum using monopolar diathermy, Harmonic scalpel and LigaSure

Abstract: Background: New hemostatic technologies are often employed in open and laparoscopic surgery to reduce duration of surgery and complications. Monopolar diathermy, Harmonic scalpel and LigaSure are routinely used in open and laparoscopic surgery for tissue cutting and hemostasis. We compared lateral thermal damage following in vivo application of 3 commonly used instruments. Methods:We used monopolar diathermy, Harmonic scalpel and LigaSure to coagulate and divide the peritoneum of patients who underwent median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 17 publications
3
64
0
2
Order By: Relevance
“…Harmonic and LigaSure) perform coagulation hemostasis by generating heat at the tip of the device. However, unexpected secondary organ damage can occur by thermal injury (12)(13)(14)(15)(16)(17)(18). Therefore, it is necessary to maintain a safety margin such that heat does not directly spread into surrounding tissues during coagulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harmonic and LigaSure) perform coagulation hemostasis by generating heat at the tip of the device. However, unexpected secondary organ damage can occur by thermal injury (12)(13)(14)(15)(16)(17)(18). Therefore, it is necessary to maintain a safety margin such that heat does not directly spread into surrounding tissues during coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Energy dissectors, however, have significant limitations due to the large amounts of heat they produce. These limitations lead to several intraoperative complications, such as accidental thermal trauma to blood vessels, nerves, ureters, and bowels (12)(13)(14)(15)(16)(17)(18). Furthermore, thermal instruments can unintentionally fuse adjacent layers, leading to misinterpretation of tissue layers and, subsequently, dissection into the wrong plane.…”
Section: Introductionmentioning
confidence: 99%
“…LigaSure and Harmonic scalpel were the safest and most efficient methods of tissue coagulation. Monopolar diathermy resulted in the greatest degree of thermal damage in tissues [30].…”
Section: Thermal Damage In Laparoscopy-an In-depth Reviewmentioning
confidence: 96%
“…Its lateral thermal spread is reported to be less than 1 mm [18]. After recruiting 100 patients for a comparative study of Monopolar diathermy, Harmonic scalpel and LigaSure at the department of surgery in Croatia, Družijanić [30] and team with the help of light microscopy and morphometric imaging analysis measured the width of tissue lateral thermal damage from the point of the peritoneal incision. After a peritoneal incision, the mean lateral thermal damages of monopolar diathermy, Harmonic scalpel (output power 3), Harmonic scalpel (output power 5), and LigaSure were 215.79, 90.42, 127.48, and 144.18 lm, respectively as shown in Table 2.…”
Section: Thermal Damage In Laparoscopy-an In-depth Reviewmentioning
confidence: 99%
“…Previous research showed that thermal tissue damage increased on average 1.41 times, from 90.42 µm to 127.48 µm, when the power level was increased from 3 to 5 in an ultrasonic surgical device that could control the output power level on a scale of 1 to 5 [12]. Furthermore, the position at which the inside of the blade makes contact with the tissue is not incised, forcing the surgeon to increase the output power level of the ultrasonic surgical device.…”
Section: Evaluation Of Robust Classifier Algorithm For Tissue Classifmentioning
confidence: 99%